The impact of information and communication technologies on accounting practices (Research, Society and Development, 2025)
Information and Communication Technologies (ICTs) have played a crucial role in the modernization of accounting, directly impacting compliance with regulatory and tax standards. The introduction of these digital tools has provided more agility, security and efficiency in companies' financial management, allowing specialists in the sector to optimize processes and minimize risks of non-compliance with current legislation. Given this scenario, the research sought to answer the following question: What impact have ICTs had on accounting practices? The general objective of this study was to analyze the impact of information and communication technologies (ICT) on the efficiency and excellence of accounting tasks. Specific objectives were also defined, such as identifying the main ICTs used. The method used consisted of a qualitative perspective based on a literature review, with exploratory, descriptive and explanatory characteristics. The research analyzed discussions about the effects of ICTs on the routine of accounting specialists and their repercussions on adaptation to technological changes. The results showed that Information and Communication Technologies (ICTs) in accounting have profoundly transformed professional and academic performance in the area. The automation of functional steps has increased efficiency, reduced human error and repositioned the accountant as a strategic agent in organizational decisions.